THE SIGNIFICANCE OF POLLINATION WITH THE HELP OF BEE IN INCREASE THE PRODUCTIVITY OF AGRICULTURAL CROPS AND BERRIES - A.I. Amirov; M.I. Bosimova (Scholars Digest Publishing, 2023)
This article provides information on the importance of bees in the pollination of agricultural crops, berries, improvement of yield indicators and quality, productive and quality production for seed farms.
Keywords: bee, wax, pollen, nectar, juice, insect, climate, flower, smell, fruit, honeysuckle, solyanka, ivy, sorrel, syrup, clover, vineyard, orchard. Enter.